New Techniques in Digital Holography - Picart, Pascal (Instrumentation and measurement series., 2015)
This book proposal for the "instrumentation & measurement" collection of ISTE-Wiley is devoted to special techniques in digital holography. The co-authors aim at establishing a synthetic stat-of-the-art of important advances in the field of digital holography. We are interested in detailing advances related to fundamentals of digital holography, in-line holography applied to fluid mechanics, digital color holography, digital holographic microscopy, infrared holography, special techniques in full field vibrometry and inverse problems in digital holography. This book presents advanced techniqu